Designing wearables for use in the workplace: The role of solution developers - Maren Evers; Martin Krzywdzinski; Sabine Pfeiffer (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2018)
Wearables (such as data glasses and smartwatches) are a particularly visible element of Industrie 4.0 applications. They aim at providing situation-specific information to workers, but at the same time they can also be used for surveillance and control because they generate data on the work process and sometimes even on movement patterns and vital data of the employees. Wearables technology is at an early stage of development, in which the interests and perspectives of relevant stakeholders, especially technology developers and the management, are of particular importance. This article explores the role of solution developers and their understanding of work processes in which wearables are to be used. It is based on expert interviews with solution developers, academic and company experts. The analysis shows an ambivalent understanding of work: On the one hand, it is characterized by the perception of workers as potential sources of error. It focuses on the optimization of individual workplaces and their ergonomics, while broader questions of work design and work organization are ignored. On the other hand, the technology developers see and discuss the potentials and dangers of wearables technologies with regard to individualization, data protection and control in a differentiated manner. – – Wearables (beispielsweise Datenbrillen und Smartwatches) sind ein besonders sichtbares Element von Industrie-4.0-Anwendungen. Sie sollten situationsgerechte Informationen zur Verfügung stellen, können aber zugleich auch Daten über den Arbeitsprozess - und teils sogar über Bewegungsmuster und Vitaldaten der Beschäftigten - generieren. Die Wearables-Technologie ist in einem frühen Entwicklungsstadium, in dem die Interessen und Sichtweisen der relevanten Akteure, vor allem der Technikentwickler und des Managements möglicher Anwendungsunternehmen von besonderer Bedeutung sind. Der vorliegende Artikel untersucht die Rolle der Lösungsentwickler und ihr Verständnis von Arbeit und den Arbeitsprozessen, in denen Wearables eingesetzt werden sollen. Er beruht auf leitfadengestützten Interviews mit Lösungsentwicklern. Gezeigt wird ein ambivalentes Verständnis von Arbeit: auf der einen Seite dominiert die Wahrnehmung menschlicher Arbeitskräfte als potentielle Fehlerquellen und die Fokussierung auf die Optimierung einzelner Arbeitsplätze und ihrer Ergonomie, während übergreifende Fragen der Arbeitsgestaltung und Arbeitsorganisation ausgeblendet werden. Auf der anderen Seite werden die Potentiale und Gefahren der Wearables-Technologien im Hinblick auf Individualisierung, Datenschutz und Kontrolle differenziert gesehen und diskutiert.
Keywords: J53; M54; O33; 330; industrie 4.0; technology; developers; labor process; optimization; Industrie 4.0; Technologie; Technologieentwicklung; Arbeitsprozess; Optimierung